Investigating Molecular Determinants of Cancer Cell Resistance to Ionizing Radiation Through an Integrative Bioinformatics Approach - Toy, Halil Ibrahim; Karakülah, Gökhan; Kontou, Panagiota I.; Alotaibi, Hani; Georgakilas, Alexandros G.; Pavlopoulou, Athanasia (Frontiers in Cell and Developmental Biology, 2021)
Eradication of cancer cells through exposure to high doses of ionizing radiation (IR) is a widely used therapeutic strategy in the clinical setting. However, in many cases, cancer cells can develop remarkable resistance to radiation. Radioresistance represents a prominent obstacle in the effective treatment of cancer. Therefore, elucidation of the molecular mechanisms and pathways related to radioresistance in cancer cells is of paramount importance. In the present study, an integrative bioinformatics approach was applied to three publicly available/accessible transcriptome datasets. These data were investigated in order to identify genes with significantly altered expression between radioresistant and corresponding radiosensitive cancer cells. Through rigorous statistical and biological analyses, a set of 36 genes was identified. These genes, primarily implicated in DNA damage repair, oxidative stress, cell pro-survival and apoptotic pathways, could serve as potential diagnostic markers in cancer cell radioresistance. Our findings could be potentially utilized in the laboratory and clinical setting for optimizing tumor response and cancer cell susceptibility to radiation.